2012
DOI: 10.1002/jmri.23704
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis based on dynamic contrast‐enhanced MRI for evaluating tumor response to preoperative therapy for oral cancer

Abstract: Both the increase of the v(e) and the elevation of permeability (K(trans) ) were indicative of a good tumor response to CRT. The pharmacokinetic analysis had potential for monitoring the histopathological response to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 30 publications
6
41
2
Order By: Relevance
“…These changes were increased with the number of fractions delivered, thus, were radiation induced. Similar CTN changes were not observed (,3%) in the spinal cords and NSTs, where radiation doses were substantially lower than those in the GTVs and parotid glands (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy vs 75-65 Gy in maximum doses). The observed CTN change was highly patient specific.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These changes were increased with the number of fractions delivered, thus, were radiation induced. Similar CTN changes were not observed (,3%) in the spinal cords and NSTs, where radiation doses were substantially lower than those in the GTVs and parotid glands (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Gy vs 75-65 Gy in maximum doses). The observed CTN change was highly patient specific.…”
Section: Discussionsupporting
confidence: 60%
“…25 Tumours that demonstrated CTN reduction may represent regions of improved oxygenation and sensitivity to radiationinduced damages. [24][25][26] The mechanisms of underlying radiationinduced CTN change in the parotid glands remain even more unclear. Heo et al 27 found that both age and obesity are closely correlated with the size and CTN of the major salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Using the DCE dynamic dataset, we calculated the DCE perfusion parameters K trans (the volume transfer constant between the blood plasma and the EES), v p (the plasma volume fraction) v e (the volume of EES per unit volume of tissue), K ep (the ratio of K trans to v e ) according to the method described based on the two-compartment model; the details of this model are described elsewhere [14]. All DCE parameters were obtained on a pixel-by-pixel basis, and all DCE parameter maps were also obtained on a pixel-by-pixel basis.…”
Section: Dce Perfusion Data Calculationmentioning
confidence: 99%
“…The procedure used in this manuscript was described in a previous article, 15,20,21 and its main principles were as follows: the first procedure was to estimate the pre-contrast T 1 map using image data with two different flip angles 21 and to estimate the dynamic T 1 maps using the methods described by Daldrup et al 22 The second procedure was to convert the difference of 1/ T 1 into the concentration of the CM by assuming a linear relationship between them. In this study, we set the r 1 relaxivity of the CM to 4.5 mM s…”
Section: Tofts and Kermode Model Analysismentioning
confidence: 99%
“…10 In the HN region, the pharmacokinetic analysis by DCE-MRI was proven to be useful for a differential diagnosis, 11 early prediction of the response and monitoring the effects of chemotherapy and radiotherapy. [12][13][14][15] However, the correlations between the pharmacokinetic parameters of the primary site and the clinical stage have been assessed in only limited studies. We have found two studies of the correlations between the quantitative parameters and clinical stage of nasopharyngeal cancer; however, the results of these studies were conflicting.…”
mentioning
confidence: 99%